Wetland Restoration Progress 39 Years After Canal Backfilling - Turner, R. Eugene (Frontiers in Ecology and Evolution, 2022)
Dredging to create canals and channels in wetlands is widespread and is a major cause of dramatically high wetland loss rates in coastal Louisiana. The dredged material placed alongside the canal forms continuous levees and can be dragged back into the canal to start wetland restoration (backfilling) but is rarely done. Thirty-three canals backfilled in the 1980s as opportunistic permit requirements were examined to determine their re-vegetation after 39 years. Sixteen of the 33 disturbed areas are now mostly restored to wetlands, and seventeen were compromised by re-dredging and other factors such as being surrounded by other canals or embedded within water level control structures. Success occurred where the natural hydrology was not artificially constrained by these structures. The re-vegetation of these 16 canals were compared to backfilled canals in the Barataria Preserve of the Jean Lafitte Historical National Park. The spoil bank was restored wetland habitat within a few years, and the open water of the canal was 70 percent re-vegetated after 39 years if there was no soil ‘plug’ placed at the canal entrance during backfilling. Backfilling canals can be done on the 27 thousand abandoned canals across this coast for a low cost compared to other restoration strategies.